Experimental Study on Physicochemical Properties of a Shear Thixotropic Polymer Gel for Lost Circulation Control - Jingbin Yang; Yingrui Bai; Jinsheng Sun; Kaihe Lv; Jinliang Han; Liyao Dai (Gels, 2022)
Polymer gel lost circulation control technology is a common and effective technique to control fractured lost circulation. The performance of a lost circulation control agent is the key to the success of lost circulation control techniques. In this study, rheological tests were used to study the physical and chemical properties of a shear thixotropic polymer gel system, such as anti-dilution, high temperature resistance and high salt resistance. The results showed that the shear thixotropic polymer gel system had the ability of anti-dilution, and the gel could be formed under a mixture of 3 times volume of heavy salt water and 3/7 volume white oil, and could keep the structure and morphology stable. Secondly, the gel formation time of shear thixotropic polymer gel system could be controlled and had good injection performance under the condition of 140 °C and different initiator concentrations. Meanwhile, the shear thixotropic polymer gel system had the ability of high temperature and high salt resistance, and the gel formation effect was good in salt water. When the scanning frequency was 4 Hz and the temperature was 140 °C, the storage modulus (G′) of the gel was 4700 Pa. The gel was dominated by elasticity and had excellent mechanical properties. By scanning electron microscope observation, it was found that the shear thixotropic polymer gel system had a stable three-dimensional reticular space skeleton under the condition of high salt, indicating that it had excellent ability to tolerate high salt. Therefore, the shear thixotropic polymer gel had high temperature and high salt resistance, dilution resistance and good shear responsiveness. It is believed that the results presented in this work are of importance for extending real-life applications of shear thixotropic polymer gel systems.